Impact of pre-slaughter factors on welfare of broilers. (December 2020) - Saraiva, Sónia; Esteves, Alexandra; Oliveira, Irene; Mitchell, Malcolm; Stilwell, George
ABSTRACT: Pre-slaughter factors adversely affecting bird welfare were studied at the slaughterhouse. The incidence of dead on arrival (DoA), bruises and dehydration was investigated in 64 different mixed-sex batches of broilers coming from 64 different farms rearing fast-growing genotypes (Ross or Cobb). The effects of catching team, method of catching, time of day for catching and transport, density per cage, transport duration, transport distance, lairage duration and water withdrawal were considered. The average DoA was 0.29%, ranging from 0.02% to 1.89% per batch. DoA rate has a higher probability of increase with the increase in transport distance (t=2.142; P =0.037; estimate=0.009) and with catching the birds after midnight (t=-2.931; P =0.005; estimate=0.022). Longer transport durations for birds caught after midnight as well as longer lairage durations for birds caught after midnight are associated with the increase of DoA rate. Bruises were observed in 3.37% of birds, ranging from 0.43% to 8.29% per batch. Bruises occurred mostly on wings (3.06%), followed by legs (0.19%) and breast (0.12%). A higher percentage of bruises occurred in batches with more birds per transport crate (t=2.185; P =0.029; estimate=0.001). Dehydrated carcasses were observed in 22 out of 64 batches, accounting for 2.68% of condemnations. Signs of dehydration on carcasses were more frequently observed in batches subjected to longer withdrawal durations. Short transport distances, catching the birds before midnight and doing the transport by night are crucial in decreasing the DoA rate. Catching and crating processes seem to be responsible for the increase of percentage of bruises. Pre-slaughter operations should be adequate planned namely, transport and lairage durations, catching period and crating procedure in view to reduce negative effects on animal welfare.